2022
DOI: 10.3390/ph15070802
|View full text |Cite
|
Sign up to set email alerts
|

Impact of PCSK9 Inhibition on Proinflammatory Cytokines and Matrix Metalloproteinases Release in Patients with Mixed Hyperlipidemia and Vulnerable Atherosclerotic Plaque

Abstract: Background: Atherosclerosis is a disorder in which, in addition to high cholesterol levels, several plasma factors play a significant role in its development. Among these cytokines and molecules are interleukin 6 (IL-6), interleukin 18 (IL-18), tumor necrosis factor α (TNF-α), metalloproteinase 2 (MMP-2), and metalloproteinase 9 (MMP-9), all of which may contribute to the stabilization of atherosclerotic plaque. The purpose of this study was to determine the effect of advanced lipid-lowering therapy on the lev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 54 publications
0
14
0
Order By: Relevance
“…We also noticed a complementary pattern after bosentan and atorvastatin in the modulation of inflammatory mediators, focusing on TNF-a and MCP-1. Experimental and clinical data have supported the relationship of inflammation with atherosclerosis development and progression [41]. Previous studies have reported reduction of two multifunctional inflammatory agents, TNF-a and MCP-1 after statin administration [42,43].…”
Section: Discussionmentioning
confidence: 92%
“…We also noticed a complementary pattern after bosentan and atorvastatin in the modulation of inflammatory mediators, focusing on TNF-a and MCP-1. Experimental and clinical data have supported the relationship of inflammation with atherosclerosis development and progression [41]. Previous studies have reported reduction of two multifunctional inflammatory agents, TNF-a and MCP-1 after statin administration [42,43].…”
Section: Discussionmentioning
confidence: 92%
“…Indeed, hs-CRP, a known marker of low-grade inflammation, is not affected by treatment with PCSK9i 33 . On the other hand, selected reports showed that treatment with PCSK9i might decrease circulating levels of IL-6 and of other cytokines 34 , 35 . Interestingly, also IL-6 inhibition has been reported to decrease circulating levels of PCSK9 protein 15 , possibly suggesting a bidirectional relationship.…”
Section: Discussionmentioning
confidence: 99%
“…Both canakinumab and PCSK-9 inhibitors have anti-inflammatory effects. Moreover, PCSK-9 inhibitors also have an inhibitory effect on MMP-2, but cannot inhibit MMP-9 [ 30 ]. So, the mechanism by which canakinumab and PCSK-9 inhibitors stabilize plaques may be different from metformin.…”
Section: Discussionmentioning
confidence: 99%